Clear Cell Sarcoma of the Kidney (CCSK) With BCOR-CCNB3 Fusion: A Rare Case Report With a Brief Review of the Literature. (March 2023) - Dorwal, Pranav; Abou-Seif, Claire; Ng, Jessica; Super, Leanne; Chan, Yuen; Rathi, Vivek
Pediatric renal tumors are a rare entity and majority of these tumors are accounted for by Wilms tumor. The second most common renal tumor is clear cell sarcoma of the kidney (CSSK). Most of the CSSK have either BCOR -internal tandem duplication (ITD) or YWHAE-NUTM2B/E fusion. The sarcomas with BCOR-CCNB3 fusion are well documented in soft tissue and bone tumors, but are extremely rare in the pediatric renal setting. We are reporting an extremely rare case of pediatric clear cell sarcoma of the kidney (CSSK) with BCOR-CCNB3 fusion, which was a diagnostic challenge on morphological grounds. A final diagnosis could only be reached after multiple reviews and NGS based RNA fusion testing. We have also performed a brief review of literature which revealed eight (8) other cases of this rare entity.